Os sentidos e significados atribuídos por uma professora aos conhecimentos prévios de seus educandos em ciências naturais - Nagoski, Rosemeire (2008)
The present research has as objective, to analyze the sense and meanings attributed for a teacher to the previous knowledge of her students in the lesson of Natural Sciences. This study it is justified producing a knowledge than can contribute for a better understanding of as the teachers mean the previous knowledge, for favoring an advance in the reflections on the teacher´s work and a possible improvement in the process of learning of the contents in Natural Sciences. So that the objetctive could be reached, we mainly opt to the theoretic-methodological on basead in the socio-historical perspective and in the constructos elaborated for Vygotski and its collaborators. Thus, the socio-historical perspective contributed to analyze the information gotten by means of a research of qualitative character, having as instruments the history of life, the filming of the lesson and the semi-structuralized interview. Our research contributed to signal the necessity of new research to the education of sciences, that prioritize the formation of the teachers in activity, from the sense for them attributed to the previous knowledge of their students. Moreover, the data also show that the teacher demonstrates, in their pedagogical practical in her stories, that the existence of the previous knowledge of her students does not ignore completely. However, they lack theoretical and methodological subsidies so that it can configure the previous knowledge in real reasons, that the ligt one to improve and to facilitate the learning of the students. To invest in research that configures the disclosed sense here in reasons for ways of methodologic interventions, becomes a necessity in Teaching of Sciences